Formulation, box-behnken optimization, and evaluation of lurasidone HCl-loaded ethosomal gel for transdermal delivery - Sesha Sai Durga Manyam; Shailaja Pashikanti (Creative Pharma Assent, 2026)
Background: Lurasidone HCl is an antidepressant drug, which is available in solid dosage form in the market. The drug lurasidone HCl in the tablet form shows poor oral bioavailability, which is only 9- 19%. Therefore, an alternative dosage form, such as ethosomes, is preferred. Methodology: The thin film hydration technique was used to formulate ethosomes. A Box-Behnken design was used to optimize the formulation, with statistical and graphical analyses of the response surface plots. Ethanol (X1), phosphatidylcholine (X2), and penetration enhancer (X3) were selected as the independent variables, and the dependent variables were vesicle size (Y1), zeta potential (Y2), and entrapment efficiency (Y3). An optimized formulation was selected after characterization of ethosomes. The optimized ethosomal formulation was incorporated into a gel base. Various ratios of Pluronic F 127 and carbopol 934 were used to prepare gel formulations, which were then evaluated. Results and Discussion: Microscopic examination of formulated ethosomes shows results within the standards. After 24 hours of study, the percentage of drug permeated was 94.7 ± 0.153. A Box-Behnken design was used to prepare and optimize ethosomes. Optimized ethosomes exhibited a vesicle size of 276.8 nm, a zeta potential of -55.7 mV, and an entrapment efficiency of 90%. Carbopol gel base was used to prepare the gel and evaluated. Conclusion: The optimized ethosomal formulation was selected for preparing an ethosomal gel loaded with lurasidone HCl. The prepared gel formulations were evaluated, and all showed satisfactory results, indicating that ethosomes are the best alternative route for administering lurasidone HCl.